Tawakal and Life Optimism for Divorced Married Couples: A Case Study in Medan, Satria Village, Bekasi City, West Java Province - Alifatuzzahroh, Wafa; Tasman, Alfadhli (El-Usrah: Jurnal Hukum Keluarga, 2023)
Marriage is a relationship between a man and a woman that is commanded in Islam. Among the purposes of marriage is to meet the various primary needs of human beings so that they can lead a better, calm and purposeful life (litaskunu ilaiha). However, along the way, there are often various problems that in some cases lead to divorce or separation. Divorce occurs due to various problems in the marriage, causing trauma, depression, loss of optimism in life and so on. The various negative impacts of divorce must certainly be faced in various ways so that the person concerned can rise from all the lags to continue to realize various plans and targets in his life. This research uses empirical legal methods using Islamic legal approaches as an analytical tool. Data were collected using in-depth interviews and documentation studies, interviews with informants of divorced parties both husband and wife. The informants in this study consisted of 5 people distinguished by 3 females and 2 males. The research concludes that trust is an important instrument in increasing faith after divorce. The majority of respondents said that putting their trust in post-divorce can increase faith. The informant said that post-divorce trust has an important role in strengthening self-mentality, increasing resilience, and building a positive mindset.